2014
DOI: 10.1016/j.rboe.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Importance of radiological studies by means of computed tomography for managing fractures of the tibial plateau

Abstract: ObjectivesTo evaluate the concordance among knee surgery specialists regarding the classification and surgical technique indicated in cases of tibial plateau fracture, using conventional radiographs and computed tomography.MethodsForty-four patients with fractures of the tibial plateau shown on radiographic and tomographic images were selected. These were evaluated by specialists at two different times, with an interval of seven days. On the first occasion, the specialists only had access to the radiographs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Other studies have observed unsatisfactory K indices (near 0.38) in inter-observer analysis 2 , 15 and satisfactory kappa values (0.68) in intra-observer analysis 2 for this classification, which makes clear that the correlation value decreases when the evaluation is between the evaluators. In this study, the concordance results are similar to results obtained in intra-observer analysis for Schatzker classification.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies have observed unsatisfactory K indices (near 0.38) in inter-observer analysis 2 , 15 and satisfactory kappa values (0.68) in intra-observer analysis 2 for this classification, which makes clear that the correlation value decreases when the evaluation is between the evaluators. In this study, the concordance results are similar to results obtained in intra-observer analysis for Schatzker classification.…”
Section: Discussionmentioning
confidence: 67%
“…These results are supported by the literature, which presents similar results, with mild to moderate agreement. [6][7][8][9][10]13,[21][22][23][24] Since CT is indispensable for the application of the Kfuri classification, in our study, the evaluators used tomographic and radiographic images to classify by the Schatzker system. The importance of using CT to increase the reliability of the Schatzker classification is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…15,21,25,26 A recent study investigated the effect of the addition of 3D tomographic images on the classification of tibial plateau fractures, concluding that the addition of the third dimension did not improve the reproducibility of the system; in fact, the use of 2D images alone had higher agreement. 14 Although the role of CT in the inter-and intraobserver agreement of tibial plateau fractures still needs to be determined, 24 this tool proved to be fundamental in choosing the surgical access route, especially in lesions with coronal orientation. 15,27 Previous studies evaluating tibial plateau fractures reported that the experience of the observers did not influence the degree of reliability of the classifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations